PENGARUH WORK LIFE BALANCE DAN SETRES KERJA TERHADAP KINERJA KARYAWAN PADA PABRIK BERAS RICE IKA PUTRA LUWU TIMUR - Kadek Eva Sulystyawati; Muhammad Kasran; Suparni Sampetan (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to evaluate and explore the relationship between work life balance factors and stress levels with employee performance at the IKA PUTRA LUWU EAST rice factory. In this study, 126 people have been selected as sample. This hypothesis was tested using multiple linear regression analysis using the SMART PLS application. The results showed that work life balance and work stress levels had a significant positive effect on employee performance. Kata Kunci : Work Life Balance, Work Setres, Employee Performance